Empowering Communities Through Health Education: Raising Awareness On Microplastic Pollution And Prevention In Malang - Zaqqi Ubaidillah; Chairul Huda Al Husna; Elok Martha Salsabhila; Sindi Amala Putri; Putri Parmitha Dwi (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Background: Microplastic pollution is a significant environmental and public health issue in Indonesia, including Malang, where public awareness about its dangers remains limited. Aims: This community service program aimed to enhance knowledge about the dangers of microplastics and preventive measures through health education. The program was attended by 48 participants, consisting of 18 men and 30 women, with an average age of 54 years. Educational backgrounds included 67% high school graduates and 33% university graduates. Method: Pre-test assessments revealed a low baseline knowledge level, with an average score of 56.4. Following the educational intervention, the post-test average score increased to 76.7, demonstrating a 20.3-point improvement. Result: The significant increase in knowledge highlights the effectiveness of tailored health education programs. Factors contributing to the success included the use of audience-specific teaching methods and practical demonstrations. Women represented a larger proportion of participants, reflecting their active role in health-related educational activities. Conclusion: The findings suggest that health education can effectively bridge knowledge gaps and serve as a foundation for promoting sustainable behavior changes, such as reducing single-use plastic consumption and improving waste management practices. Despite the positive results, follow-up activities and community engagement are essential to sustain and reinforce learning outcomes. Future interventions should focus on behavioral changes and involve diverse demographic groups to maximize community-wide impact. This program underscores the importance of continuous education and practical actions in addressing microplastic pollution and mitigating its long-term effects on health and the environment.